Meningkatkan Kompetensi Guru Matematika dalam Penggunaan Alat Peraga Melalui Supervisi Inspeksi - Erliadi (Jurnal Pendidikan Penggerak, 2023)
The purpose of this study to determine the increase competency of mathematics teachers in using visual aids through inspection supervision at the target schools in semester II of the 2022/2023 academic year. This research designed in the form of School Action Research which was carried out in two cycles, as the subjects were mathematics teachers in schools assisted by researchers as many as 28 teachers. The results showed that the competency score in the use of teaching aids was 91-100 or category A in the initial conditions there were no, in the first cycle there were 5 people or 17.86%, while in the second cycle increased to 9 teachers or 32.14%. In the initial conditions there were 3 teachers or 10.71% of the total teachers having scores between 76-90% Good category (B), in cycle I there were 12 teachers or 42.86% of the total teachers having grades between 76-90 % Good category (B), while in cycle II it increased to 18 teachers or 64.29% of the total number of teachers. In the initial conditions there were 6 teachers or 21.43% with a score of 60-75 Enough category (C), while in cycle I there were 7 teachers or 25.00% of the total number of teachers with a score of 60-75 Enough category ( C), while in cycle II there was only 1 teacher left with a score of 60-75 Enough category (C).